“The Modern Scientific Tradition and its Contribution to Economic Regression in Africa.” - Lauer, H. (.” Philosophy and Social Change (ed.) Temisan Ebijuwa. -Ibadan: Hope Publications, pp. 121-146., 2007)
A false ‘ideology of incapacity’ dominates current mainstream socio-economic literature about Africa carried over from August Comte’s 18th century formula for social progress. To presume there is movement along a universal vector of increasing civilisation leaves unchallenged the most egregious inaccuracies about African societies that dominate global discourse about economic development and health crises in Africa. This paper corrects the record of where contributions to scientific progress actually originate, and to whom the legacy of scientific benefits and social goods actually belongs.
Keywords: Modern science; Eurocentricism; HIV/AIDS in Africa; Tradition vs. Modernity